PENGARUH KOMUNIKASI, LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. KREASICIPTA AKSESDASISINDO JAKARTA - Nona Aprillina; Dr. Ismail Razak, M.Si. (Jurnal Ekonomi dan Industri, 2021)
The purpose of this study was to analize the effect of communication, job environment, and job load on job satisfaction of the PT. Kreasicipta Aksesdasisindo, Jakarta. Primary data was obtained from employee of the PT. Kreasicipta Aksesdasisindo, Jakarta through admission filling of questionnaire by using scale of Likert. Data analysis technique used in this research is simple linear regression and multiple linear regression. The results of this study indicated that communication, job environment, and job load positively and significant influenced the job satisfaction of the PT. Kreasicipta Aksesdasisindo, Jakarta.